Identification of biotic agents associated with chickpea yellowing syndrome (CYS) in Argentina - Pugliese, Bruno Daniel; Edwards Molina, Juan Pablo; Camiletti, Boris Xavier; Rodriguez Pardina, Patricia; Pastor, Silvina Estela (American Phytopathological Society (APS), 2024)
Poster